Developing a valid meal assessment tool for hospital patients. (1st January 2017) - Hannan-Jones, Mary; Capra, Sandra
Abstract: Patients' perspectives of meal items are critical in supporting effective decisions about meal provision in hospitals. The objective of this research was to develop a valid meal assessment tool (MAT), to quickly and accurately assess patient's views on meal items, for ultimate use in a large multi-centre trial. Nine iterations of the meal assessment tool were tested for content and construct validity in a large acute care hospital to determine wording, number scale and physical orientation for responses. Patients were interviewed to assess content validity, ease of completion, timing and assistance requirement. Following expert feedback, the resulting tool consisted of a 7 point scale measuring three meal components (meat, starch and vegetable), with ratings for flavour and taste combined, appearance and quality. Measures of overall satisfaction, meal expectation, age and gender were included for direct comparability with the valid published Acute Care Hospital Foodservice Patient Satisfaction Questionnaire (ACHFPSQ). Three hundred and four surveys were completed in the development process (77% response), 53% male, mean age 56 years. Best completion rates were by interview with completion times of 2–5 min. The tool was then made available in a large multi-centre meal assessment project (n = 14, 500) and was able to detect differences between variations of the same meal and between the same ingredient prepared in alternative ways. The MAT proved successful in discriminating meal components in terms of quality, taste and appearance and is useful for those planning and assessing meals in a variety of healthcare settings.